2008
DOI: 10.1111/j.1463-1326.2008.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic insulin aspart 30 in the treatment of elderly patients with type 2 diabetes: a subgroup analysis of the PRESENT Korea NovoMix®study

Abstract: In this subanalysis of Korean elderly patients with type 2 diabetes inadequately controlled on their previous therapies, treatment with BIAsp30 offered improvements in glycaemic control and was well tolerated. Body weight gain was minimal with BIAsp30, and treatment satisfaction among these patients appeared to be high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
2
9
1
2
Order By: Relevance
“…In contrary to previous reports on BIA studies conducted in Korea (Kor-A1chieve® reference, [5,7]), weight gains by the initiation of insulin were significant in this study.…”
contrasting
confidence: 99%
“…In contrary to previous reports on BIA studies conducted in Korea (Kor-A1chieve® reference, [5,7]), weight gains by the initiation of insulin were significant in this study.…”
contrasting
confidence: 99%
“…Similar findings emerged from the PRESENT study, a large observational study in almost 22,000 patients with T2D. Data were recently published from the Chinese, Korean, and Indian cohorts [29][30][31]. Gao et al [29] reported that the insulin-treated subgroup in the Chinese PRESENT cohort (n=2392) experienced a −1.8% improvement in HbA 1c after switching to BIAsp 30; the majority (83%) of this group were previously treated with premixed insulin, which although unspecified could be presumed to be largely human premixed insulin.…”
Section: Premixed (Biphasic) Analoguessupporting
confidence: 76%
“…Reported minor hypoglycemia was reduced from 12.3 to 4.2 events per patient per year in the insulin-treated group. Similarly, improvements in glycemic control were reported from the PRESENT study by Jang et al [30] from 5,828 Korean subjects (HbA 1c change −1.4% and −1.2% in patients <65 years and ≥65 years, respectively) and by Sharma et al [31] from 3,559 Indian subjects (-1.94%).…”
Section: Premixed (Biphasic) Analoguessupporting
confidence: 63%
“…The Chinese, Indian, Iranian, Italian and Korean cohorts of the IMPROVE™ and PRESENT™ studies have been published. [93100] These subgroup analyses of large multinational observational studies are a useful resource by providing a way to benchmark local outcomes against those achieved globally. Similarly, smaller single-country observational studies examining the initiation of BIAsp 30, such as those carried out in the UK and Denmark, provide physicians with clinically relevant information for the type of patients that they see in daily practice.…”
Section: Clinical Evidence Translating To Clinical Practicementioning
confidence: 99%